Advertising communication in the fashion industry: branded content, the case of fashion films - Arbaiza Rodriguez, Francisco (2018)
This article addresses one of the new advertising trends, branded content, a formula that goes beyond product placement and proposes relevant content to the consumer. Specifically, is analyzed the case of fashion films, an advertising format that has broken out in the sector of fashion and luxury products with great success, and whose objective is to generate content specifically for a particular fashion brand, in which beauty and aesthetic predominates, but above all, allows to communicate the values and personality of the brand and thus connect with the consumer.